Efficiency of wastewater purification in medium sand with a lightweight expanded clay aggregate assisting layer - Marek Kalenik; Piotr Wichowski; Marek Chalecki; Adam Kiczko (Journal of Water and Land Development, 2023)
The objective of this experimental study was to examine whether an assisting layer of lightweight expanded clay aggregate (LECA) of the granulation 1–4 mm, introduced into a subsoil, is able to improve an efficiency of removal of total nitrogen and total phosphorus from domestic wastewater. In the investigations, an assisting 0.10 and 0.20 m thick LECA layer was applied. It has been observed that the effectiveness of removal of total suspended solids (TSS), total nitrogen and total phosphorus from wastewater as well as the level of biochemical oxygen demand ( BOD 5) and chemical oxygen demand ( COD) is in accordance with the Polish standards on wastewater disposal into grounds and surface water. The performed experiments showed that the effectiveness of raw wastewater purification for the medium sand soil bed with the 0.20 m thick assisting LECA layer is higher than for the 0.10 m thick assisting layer. In the medium sand soil bed with the 0.20 m thick assisting LECA layer, the removal efficiency regarding total nitrogen increased by 20.6%, total phosphorus by 5.2%, ammonium nitrogen by 8.8% and TSS by 5.3%, and reduction efficiency regarding BOD 5 increased by 1.7% and COD by 2.3% with relation to the 0.10 m thick assisting LECA layer (all percentages – in average). The results of the experiment showed that the LECA with the granulation 1–4 mm can be used to assist in removal of total nitrogen and total phosphorus from wastewater with application of infiltration drainage.